Chilean institutional policies and multi-level agents: Challenges from the COVID-19 pandemic and carbon footprint - Bergamini, Kay; Ojeda, Carolina G.; Gutiérrez, Patricia; Salazar, Gonzalo; Curillán, Christian (Frontiers in Communication, 2023)
Introduction As a result of the increasing number of multilateral agreements that Chile has signed, different sectors of consumption have become sources of emissions. In this context attempts to implement guidelines to address this issue have been made. Nevertheless, international policies such as sustainable development goals (SDG) 11–12 often generate dissonance in national and local administrations and have been approached by different instruments to reduce the effects of emissions, mostly focused on the private industrial sector. Methods This article focuses on four of the most polluted cities in south-central Chile (Coronel, Temuco, Valdivia, and Osorno). Key agents (ministries, regional government, municipalities, and civil society) from three levels of policy development were selected at three scales (national, regional, and local) and interviewed considering three thematic axes: knowledge of carbon footprint areas (housing, heating, food, mobility, and energy), institutional governance, and adaptive changes due to COVID-19. Results The results show that in Chile, there is a multiscale climate governance led by the Ministry of the Environment (national level), followed by the regional and local levels. Citizens are then left with few capacities, which is negatively viewed. In relation to the carbon footprint and COVID-19, it can be observed that the topic of energy was more addressed at the national and regional levels. Food and energy, followed by heating and then mobility were addressed at the communal level and in civil society. Discussion Decision-making strategies and policies were discussed in this paper.